Clonal variability in black pepper hybrid Panniyur 1 - Samuel Mathew, T Pradeepkumar, D Sajith Babu, K C Aipe, (Journal of Spices and Aromatic Crops, 2003)
Forty two clones of twenty year old Panniyur 1 plants, grown as a monocrop of black pepper, were analyzed for variations in yield contributing factors as well as quality paralTIeters over a period of three years. The analysis of the data has revealed that the plants exhibited considerable amount of variability for characters under study and the standard deviation was lnore for berries spike-1 and yield. Among the quality characteristics, oleoresin exhibited more variability than piperine. From the non hierarchical Euclidean cluster analysis it is observed that the plants can be clustered ideally in to five clusters based on their mean performance. The intra and inter cluster distance was more for cluster number 4, which later culminated in Inaximuln nUlnber of plants (13) having high yield and oleoresin.